Modern Approaches to Depression: From Monoamines to Medicinal Plants and Neuromodulation (Asian Journal of Pharmaceutics (AJP), 2025)
One of the most common mental health conditions in the world, depression severely reduces social functioning,productivity, and personal well-being. Over 300 million people are impacted globally, and by 2040, it isexpected to overtake all other causes of disability. A thorough discussion of major depression, also known asmajor depressive disorder, is given here, along with an examination of its complex etiology, which includesgenetic, neurochemical, and sociocultural factors. Its pathogenesis is primarily characterized by the dysregulationof the hypothalamic-pituitary-adrenal axis, glutamatergic signaling, and monoaminergic transmitters includingdopamine, serotonin, and norepinephrine. Due to their delayed onset, adverse effects, and resistance to therapy,conventional antidepressant therapies such as selective serotonin reuptake inhibitors, serotonin-norepinephrinereuptake inhibitors, tricyclic antidepressants, and monoamine oxidase inhibitors remain first-line treatments. Inaddition, this review covers new approaches to treatment, including psychedelic-assisted therapy, brain stimulationtechniques such as electroconvulsive therapy, transcranial magnetic stimulation, deep brain stimulation, and vagusnerve stimulation and rapid-acting pharmaceuticals such as ketamine and esketamine. The use of medicinal plantssuch as Withania somnifera, Curcuma longa, Hypericum perforatum, and others demonstrates promise due to theirmulti-targeted action, safety, and accessibility. These phytochemicals modulate neurotransmitter activity, reduceoxidative stress, and support neurotrophic factors. A holistic and personalized treatment approach, integratingpharmacotherapy, neurostimulation, and complementary herbal medicine, may optimize outcomes in depressionmanagement. Addressing stigma, increasing early diagnosis, and ensuring mental health-care accessibility remainimperative. Future research should focus on novel drug targets, patient-tailored therapies, and bridging the gapbetween traditional and modern practices.